2010
DOI: 10.3892/ijmm_00000458
|View full text |Cite
|
Sign up to set email alerts
|

CpG hypermethylation of human four-and-a-half LIM domains 1 contributes to migration and invasion activity of human bladder cancer

Abstract: Abstract. We previously reported a simple technique that combines microarray data from clinical bladder cancer (BC) specimens with those from a BC cell line (BOY) treated with a pharmacologic demethylating agent (5-aza-dC). We focused on the human four-and-a-half LIM domains 1 (FHL1) gene which was selected on the basis of previous microarray data analysis. Because LIM domains provide protein-protein binding interfaces, FHL genes play an important role in cellular events, such as focal adhesion and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…These results are consistent with those of previous studies showing that FHL1 inhibits the proliferation of lung cancer cells in vitro 9 . Studies in oral cancer and bladder cancer have also found that reduced expression of FHL1 promotes tumor progression and is associated with poor prognosis 10 , 23 . These studies strongly suggest that FHL1 plays an anticancer role in the proliferation of a variety of tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of previous studies showing that FHL1 inhibits the proliferation of lung cancer cells in vitro 9 . Studies in oral cancer and bladder cancer have also found that reduced expression of FHL1 promotes tumor progression and is associated with poor prognosis 10 , 23 . These studies strongly suggest that FHL1 plays an anticancer role in the proliferation of a variety of tumor types.…”
Section: Discussionmentioning
confidence: 99%